2018
DOI: 10.1007/s00161-018-0703-1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical integration of the contravariant integral form of the Navier–Stokes equations in time-dependent curvilinear coordinate systems for three-dimensional free surface flows

Abstract: We propose a three-dimensional non-hydrostatic shock-capturing numerical model for the simulation of wave propagation, transformation and breaking, which is based on an original integral formulation of the contravariant Navier-Stokes equations, devoid of Christoffel symbols, in general time-dependent curvilinear coordinates. A coordinate transformation maps the time-varying irregular physical domain that reproduces the complex geometries of coastal regions to a fixed uniform computational one. The advancing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(108 citation statements)
references
References 48 publications
1
107
0
Order By: Relevance
“…In this paper we adopt the governing equations proposed in [9][10] in which the Navier-Stokes equations are expressed in integral contravariant form in a time-dependent curvilinear coordinate system.…”
Section: Governing Equationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper we adopt the governing equations proposed in [9][10] in which the Navier-Stokes equations are expressed in integral contravariant form in a time-dependent curvilinear coordinate system.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Equations (1) and (2) represent the general integral form of the Navier-Stokes equations expressed in a time dependent curvilinear coordinate system. The complete derivation of these equations can be found in [10]. In [9] it has been demonstrated that, by taking the limit as the volume approaches zero, the integral Equations (1) and (2) are reduced to the complete differential form of the contravariant Navier-Stokes equations in a time dependent curvilinear coordinate system that have been proposed in the literature by Luo and Bewley [12].…”
Section: Governing Equationsmentioning
confidence: 99%
See 3 more Smart Citations